Macular Pigment Distribution Responses to High-Dose Zeaxanthin Supplementation in Patients with Macular Telangiectasia Type 2 (MacTel) - Choi, Rene Y. (Retina, 2017)
PURPOSE: Analysis of macular pigment (MP) amount and distribution in patients with macular telangiectasia type 2 (MacTel) receiving oral zeaxanthin supplementation in a randomized, open-label interventional trial. METHODS: Eight MacTel patients were randomized to 10 mg or 20 mg of zeaxanthin per day. At each visit, the subjects were examined including best corrected visual acuity (BCVA), contrast sensitivity (CS), fundus biomicroscopy, color fundus photography (CFP), autofluorescence imaging (AFI), optical coherence tomography (OCT), and serum carotenoid levels. Patients were assessed at baseline and after 6, 12, 18, and 24 months of zeaxanthin supplementation. MP concentration was analyzed and calculated from AFI obtained at 488 nm excitation wavelength. Serum carotenoid levels were obtained using high-performance liquid chromatography (HPLC). RESULTS: The majority of subjects had definite increases in intensity of the macular pigment’s hypofluorescent ring, but none of them deposited macular pigment centrally at the fovea. Although some patients noted subjective improvements in vision, no objective improvements could be documented, and there were no changes in foveal OCT features. Yellowish, hypofluorescent crystals appeared in one subject’s macular region with no change in visual acuity. These inner retinal crystals disappeared several months after discontinuing her 20 mg zeaxanthin supplement. CONCLUSION: Based on our study, zeaxanthin supplementation does not result in any visual benefit in patients with MacTel, and does not re-establish a normal peaked distribution of macular pigment in the fovea. One subject developed a novel, reversible crystalline maculopathy in response to zeaxanthin supplementation that was reminiscent of canthaxanthin crystalline maculopathy.